Pengaruh Promosi dan Fasilitas Terhadap Minat Kuliah di Fakultas Agama Islam Universitas Ibn Khaldun Bogor - Muhammad Faishal Hidayat; Muhamad Azhar Alwahid; Agus Suryana (Transformasi Manageria: Journal of Islamic Education Management, 2024)
The interest in pursuing higher education is influenced by various factors, including promotional activities conducted by universities and the academic facilities offered. This study aims to analyze the effects of promotions and facilities on the interest in higher education at the Faculty of Islamic Studies, Ibn Khaldun University (UIKA) Bogor, and examine whether promotions and facilities collectively influence the interest in higher education. The research employs a quantitative approach with multiple linear regression analysis. The population comprises active students of the Faculty of Islamic Studies, UIKA Bogor, with a sample of 75 respondents. The findings indicate that both promotions and facilities significantly and collectively influence the interest in higher education by 63.7%. Facilities have a greater influence, with each 1% increase in facilities leading to a 49.2% increase in the interest in higher education. Meanwhile, each 1% increase in promotions increases the interest in higher education by 29.3%.